A pharmacokinetic study on twenty-one compounds in rat plasma by integrating UPLC-QQQ-MS/MS with GC-MS after oral administration of Suxiao Jiuxin pill - Ye Shang; Minglei Ge; Peng Zhao; Tiantian Wu; Shujie Wei; Hong Zhou; Yongping Jiang; Dandan Shang; Jun Wang; Tong Geng; Jun He (Arabian Journal of Chemistry, 2024)
Suxiao Jiuxin pill (SX) was a commonly used traditional Chinese medical preparation for treating acute myocardial infarction. However, fewer studies have been reported for comprehensively investigating the pharmacokinetic of the non-volatile and volatile chemical constituents in SX. For current study, a comprehensive and sensitive quantitation of twenty-one compounds in rat plasma was developed and validated by integrating UPLC-QQQ-MS/MS with GC-MS after oral administration of SX. The pharmacokinetic study was performed under acceptable specificity, linearity, sensitivity, precision and accuracy, recovery, matrix effect and stability. Ultimately, borneol, isoborneol, senkyunolide A, senkyunolide Ⅰ, ligustilide, ferulic acid, neocnidilide, senkyunolide H and levistolide A were detected. Their ranges of Tmax, Cmax, T1/2z and AUC (0-∞) were 0.07 ∼ 0.33 h, 5.24 ∼ 683.35 μg/L, 0.29 ∼ 1.08 h and 6.55 ∼ 474.62 μg/L*h, respectively. This study would be meaningful in better revealing the therapeutic material basis of SX. Furthermore, it could provide reference on pharmacological effect of SX against acute myocardial infarction.